Nuevos registros de patogenos fungicos de la guacamaya francesa (Senna alata (L.)) en cuba - Lopez, M.O.=700 1 Veitia, M.; Lopez, D.
(Es, En)
Ilus., 15 ref.
Keywords: CAáIA ALATA; HONGOS ENTOMOPATOGENOS; ESPECIES NUEVAS; REGISTRO; CUBA; GUACAMAYA FRANCESA